BPSD reconsidered: diagnostic considerations to preserve personhood in persons with dementia - Warren, Alison (Frontiers in Dementia, 2023)
BPSD is relatively common but profoundly disturbing to persons with dementia, their family, and caregivers. Growing recognition of the impact of BPSD on quality of life has improved recently, but assessment and management approaches are still lacking. Considerable controversy surrounding the label of BPSD has garnered a great deal of attention, with implications of its contribution to the already pervasive dementia-related stigma experienced by persons with dementia and their caregivers. This brief review aims to summarize salient viewpoints, controversies, and considerations of the assessment, management, and perception of BPSD, in an effort to offer potential recharacterizations of BPSD to promote and prioritize personhood in persons with dementia.